To what degree do the currently used physics textbooks meet the expectations? - BEKİROĞLU, FERAL (My University, 2007)
Textbooks play an important part in the instructional process. The purposes of this study were to develop an instrument to identify the characteristics of high school physics textbooks, and examine how appropriate the currently used textbooks were for teaching and learning physics. The criteria were identified and the instrument was developed with the pre-service physics teachers to evaluate the physics textbooks approved by the Turkish Ministry of Education. This study described some problems in the content and design of the physics textbooks that might be caused by the narrow criteria used by the Ministry to approve science textbooks. The criteria in this evaluation instrument would provide an empirical base in analysis of high school physics textbooks and be used by not only the Turkish Ministry but also by physics teachers and textbook evaluators from other countries. Moreover, these criteria can be modified and used in selection of appropriate textbooks of other science disciplines. © Springer Science+Business Media, Inc. 2007.